Online strain measurement during blown film extrusion using digital image correlation / Komethi Muniandy ... [et al.] - Muniandy, Komethi; Mohamad Ariff, Zulkifli; Abu Bakar, Azhar (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
Development of strain during blown film extrusion process was monitored online on the surfaces of high density polyethylene (HDPE) film. The displacement and strain were measured using Digital Image Correlation (DIC) method by following the digital or pixel changes of the marker during the film stretching process. Two different methods of creating random pattern on the surface of the blowing film were studied using a permanent black marker pen ink and grey spray paint prior to the measurement. The reliability of DIC was evaluated by verifying the measured strains and displacement results with those obtained using conventional method. Results showed that black marker pen ink was suitable for creating a random pattern on the blown film surface during extrusion process. The strain values from both conventional and DIC methods were comparable and therefore, proved that the DIC method was reliable enough to be used in a dynamic process such as blown film extrusion process.